A Generalized q-Grüss Inequality Involving the Riemann-Liouville Fractional q-Integrals. (17th August 2014) - Secer, Aydin; Purohit, S. D.; Selvakumaran, K. A.; Bayram, Mustafa
Abstract : The aim of this paper is to establish q -extension of the Grüss type integral inequality related to the integrable functions whose bounds are four integrable functions, involving Riemann-Liouville fractional q -integral operators. The results given earlier by Zhu et al. (2012) and Tariboon et al. (2014) follow the special cases of our findings.